Chemical and Physical Properties of Cassava Starch–CM-Chitosan–Acrylic Acid Gel Copolymerization by Gamma Irradiation - Gatot Trimulyadi Rekso (Universitas Gadjah Mada, 2014)
Starch is a renewable natural polymer that can be decomposed easily in the environment and can be modified to various applications such as biomedical, agricultural and pharmaceutical applications. Copolymerization of gelatinized starch–CM-chitosan and acrylic acid (AAc) in aqueous medium using γ-irradiation was carried out. The preparation conditions, such as irradiation dose and AAc concentration were investigated. The copolymers were characterized by FTIR spectroscopy, thermo-gravimetric analysis (TGA) and scanning electron microscopy (SEM). The results show that by increasing of irradiation dose the gel fraction increases till the dose of 15 kGy. Above the stating dose the gel fraction decreases. The Equilibrium Degree of Swelling (EDS) value slightly increases with increasing irradiation dose and after dose of 15 kGy is decreasing. The swelling of starch–CM-chitosan–AAc hydro gels reduced as the gel content increases. The results indicated that the optimum condition for obtaining hydro gels with desirable properties was irradiated at dose of 15 kGy. The results indicated that SEM revealed that the higher the dose, the lower the copolymer pore size. The starch–CM-chitosan–AAc copolymers have thermal stability higher than that for starch individually.